Assessment of Grid and Cloud Computing - Dhanalakshmi, S; Thenmozhi, G (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is based on several other computing research areas such as HPC, virtualization, utility computing and grid computing. The service oriented, loose coupling, strong fault tolerant, business model and ease use are main characteristics of cloud computing. Grid computing in the simplest case refers to cooperation of multiple processors on multiple machines and its objective is to boost the computational power in the fields which require high capacity of the CPU. In grid computing multiple servers which use common operating systems and software have interactions with each other. Grid computing is hardware and software infrastructure which offer a cheap, distributable, coordinated and reliable access to powerful computational capabilities. This paper strives to compare and contrast Cloud Computing with Grid Computing from various angles and give insights into the essential characteristics of both.